Oral Bioavailability, Tissue Distribution, Metabolism, and Excretion of Panduratin A from Boesenbergia rotunda Extract in Healthy Rats - Kongratanapasert T; Boonyarattanasoonthorn T; Supannapan K; Hongeng S; Khemawoot P (Dove Medical Press, 2024)
Teetat Kongratanapasert,1,2 Tussapon Boonyarattanasoonthorn,3 Kittitach Supannapan,4 Suradej Hongeng,5 Phisit Khemawoot1 1Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Samutprakarn, Thailand; 2Program in Translational Medicine, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, Thailand; 3Chulalongkorn University Laboratory Animal Center, Chulalongkorn University, Bangkok, Thailand; 4Chao Phraya Abhaibhubejhr Hospital Foundation, Prachinburi, Thailand; 5Department of Pediatrics, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Bangkok, ThailandCorrespondence: Phisit Khemawoot, Chakri Naruebodindra Medical Institute, Faculty of Medicine Ramathibodi Hospital, Mahidol University, Tel/Fax +66 28395161, Email phisit.khe@mahidol.ac.thBackground: Our previous studies in vitro and in vivo have shown anti-severe acute respiratory syndrome coronavirus 2 activity of fingerroot extract (Boesenbergia rotunda) and its phytochemical panduratin A.Aim of Study: Therefore, the objective of this study was to determine the pharmacokinetic profiles of panduratin A, as a pure compound and in fingerroot extract, in rats.Materials and Methods: Male rats were randomly divided into four groups. Rats underwent intravenous administration of 4.5 mg/kg panduratin A, a single oral administration of 45 mg/kg panduratin A, or a multiple oral administration of 45 mg/kg panduratin A-consisted fingerroot extract for 7 consecutive days. The concentrations of panduratin A in plasma, tissues, and excreta were measured by using LCMS with a validated method.Results: The rats showed no change in health status after receiving all test preparations. The absolute oral bioavailability of panduratin A administered as pure panduratin A and fingerroot extract were approximately 9% and 6%, respectively. The peak concentrations for the single oral doses of 45 mg/kg panduratin A and fingerroot extract, were 4833 ± 659 and 3269 ± 819 μg/L, respectively. Panduratin A was mostly distributed in gastrointestinal organs, with the highest tissue-to-plasma ratio in the stomach. Approximately 20- 30% of unchanged panduratin A from the administered dose was detected in feces while a negligible amount was found in urine. The major metabolites of administered panduratin A were identified in feces as oxidation and dioxidation products.Conclusion: Panduratin A from fingerroot extract showed low oral bioavailability, good tissue distribution, and partially biotransformed before excretion via feces. These findings will assist in developing fingerroot extract as a phytopharmaceutical product for COVID-19 treatment. Keywords: pharmacokinetics, tissue distribution, biotransformation, panduratin A, Boesenbergia rotunda, COVID-19